Analisis Penalaran Pada Soal Bilangan Dalam Buku Matematika Sekolah Dasar - Yulia Fadhila, Sukmawarti (CV. Pusdikra Mitra Jaya, 2023)
This study aims 1) to analyze the reasoning of number problems in mathematics books in elementary schools for low and high grades in the 2013 curriculum; 2) To find out what reasoning students use in working on math number problems at the elementary school. This research uses a qualitative approach with a descriptive type. The subject to be investigated in this study is the student book of SDN 101944 Deli Muda, Perbaungan District, Serdang Bedagai Regency. The instruments used in this study were test instruments, interviews, observation and documentation. While the data analysis technique in this study is using data analysis techniques from Miles and Huberman. Based on the results of the research, it can be concluded that based on the results of the research and discussion that has been described in chapter IV, the types of reasoning on number questions in elementary mathematics books can be concluded as follows: 1) The questions given to students for low to high grades are questions - questions that students have studied in the previous lesson in the teaching and learning process (PBM), where 83.3% of the questions are the IR reasoning type and 16.6% of the questions are the CR reasoning type; and 2) 86.58% of the questions given in mathematics books for elementary school students from low to high grades by Grafindo Media Pratama publishers were questions of the IR reasoning type and 13.42% were questions of the CR reasoning type.